A review of soil waterlogging impacts, mechanisms, and adaptive strategies - Zhang, Yusen; Chen, Xiaojuan; Geng, Shiying; Zhang, Xiujuan (Frontiers in Plant Science, 2025)
Waterlogging is a major abiotic stress affecting plant growth and productivity. Regardless of rainfall or irrigated environments, plants frequently face waterlogging, which may range from short-term to prolonged durations. Excessive precipitation and soil moisture disrupt crop growth, not because of the water itself but due to oxygen deficiency caused by water saturation. This lack of oxygen triggers a cascade of detrimental effects. Once the soil becomes saturated, oxygen depletion leads to anaerobic respiration in plant roots, weakening their respiratory processes. Waterlogging impacts plant morphology, growth, and metabolism, often increasing ethylene production and impairing vital physiological functions. Plants respond to waterlogging stress by altering their morphological structures, energy metabolism, hormone synthesis, and signal transduction pathways. This paper synthesizes findings from previous studies to systematically analyze the effects of waterlogging on plant yield, hormone regulation, signal transduction, and adaptive responses while exploring the mechanisms underlying plant tolerance to waterlogging. For instance, waterlogging reduces crop yield and disrupts key physiological and biochemical processes, such as hormone synthesis and nutrient absorption, leading to deficiencies of essential nutrients like potassium and calcium. Under waterlogged conditions, plants exhibit morphological changes, including the formation of adventitious roots and the development of aeration tissues to enhance oxygen transport. This review also highlighted effective strategies to improve plant tolerance to waterlogging. Examples include strengthening field management practices, applying exogenous hormones such as 6-benzylaminopurine (6-BA) and γ-aminobutyric acid (GABA), overexpressing specific genes (e.g., ZmEREB180, HvERF2.11, and RAP2.6L), and modifying root architecture. Lastly, we discuss future challenges and propose directions for advancing research in this field.